Ethical legitimacy of criminal law - Szczucki, Krzysztof (International journal of law, crime and justice, 2018)
The paper argues that the model of ethical legitimacy of criminal law should be welcomed. Two types of legitimacy may be recognized - primary and secondary. Primary legitimacy derives its validity from its coherence with ethical principles of responsibility, thus together shaping a message about what is right and wrong. Under this interpretation, severing of the ties between law and ethics does not mean that criminal law ceases to bind in the formalistic sense. Clearly, however, in such a case it loses one of the fundamental rationales for its validity, and it becomes increasingly more difficult to enforce it. Secondary legitimacy, contemporarily often considered the only one, reposes the validity of criminal law in decisions of an authorized legislator, thus deciding upon the bindingness of normative determinations (however, other constructs may also perform this function). Justifiability of ethical legitimacy of criminal law, where the principle of dignity of the person is dominant, is shown by reference to the example of unconscious non-intentionality. Of course, ethical legitimacy of criminal law and the choice of a constitutional anthropological vision have implications not only for this institution. Others include the theory of a criminal act, attempt, assignment of liability for a consequence, defences and errors.